2012
DOI: 10.1016/j.cell.2012.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Scl Represses Cardiomyogenesis in Prospective Hemogenic Endothelium and Endocardium

Abstract: Summary Endothelium in embryonic hematopoietic tissues generates hematopoietic stem/progenitor cells; however, it is unknown how its unique potential is specified. We show that transcription factor Scl/Tal1 is essential for both establishing the hematopoietic transcriptional program in hemogenic endothelium and preventing its misspecification to a cardiomyogenic fate. Scl−/− embryos activated a cardiac transcriptional program in yolk sac endothelium, leading to the emergence of CD31+Pdgfrα+ cardiogenic precurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
148
1
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(173 citation statements)
references
References 54 publications
(57 reference statements)
16
148
1
8
Order By: Relevance
“…5 A-C). TAL1 is commonly known as a transcriptional activator in various hematopoietic lineages (39), although a role for gene repression has recently been described in a different cellular context (embryonic endothelium) (45). Our analysis suggested that TAL1 might also contribute to transcriptional repression in hematopoietic cells by modulating the activity of poised enhancers.…”
Section: Computational Analysis Identifies Tal1 In Regulating H3k27me3mentioning
confidence: 71%
See 1 more Smart Citation
“…5 A-C). TAL1 is commonly known as a transcriptional activator in various hematopoietic lineages (39), although a role for gene repression has recently been described in a different cellular context (embryonic endothelium) (45). Our analysis suggested that TAL1 might also contribute to transcriptional repression in hematopoietic cells by modulating the activity of poised enhancers.…”
Section: Computational Analysis Identifies Tal1 In Regulating H3k27me3mentioning
confidence: 71%
“…One of the most enriched GO biological processes was "regulation of heart contraction" [false-discovery rate (FDR) q-value = 1.1E-3], and one of the strongly associated mouse phenotypes was "congestive heart failure" (FDR q-value = 7.4E-4) (SI Appendix, Table S4). Interestingly, in the aforementioned study (45), the genes repressed by TAL1 were also associated with cardiomyogenesis. Despite the differences between the two model systems, we observed a significant overlap (58 of 965, P = 5.2E-6) between the genes harboring a poised enhancer in ProE cells and those up-regulated by TAL1 depletion in embryonic endothelium (45).…”
Section: Computational Analysis Identifies Tal1 In Regulating H3k27me3mentioning
confidence: 99%
“…The transcription factor SCL is critically required for establishing hemogenic endothelium [50,[87][88][89]. Importantly, SCL is not required once the hemogenic endothelium has formed, placing it upstream of Runx1 [28,50,90].…”
Section: Sclmentioning
confidence: 99%
“…Importantly, SCL is not required once the hemogenic endothelium has formed, placing it upstream of Runx1 [28,50,90]. Recently, loss of SCL was shown to initiate a cardiac-related transcriptional program in the yolk sac, indicating that SCL expression represses the cardiac program [89]. Conditional deletion of SCL indicated that this occurs early in development, possibly already in the hematopoietic-fated SCL expressing mesoderm.…”
Section: Sclmentioning
confidence: 99%
“…During embryogenesis, hematopoietic cells originate from the lateral plate mesoderm in an ordered program of development occurring in conjunction with cells of the cardiovascular system and share a common precursor, the hemangioblast [8][9][10][11]. The study of the hemangioblast, hemogenic endothelial cells and endothelialto-hematopoietic transition [12][13][14] is critical to the understanding of related pathologies and for the development of a robust and reliable in vitro method of ESC differentiation toward cells, such as red blood cells (RBCs), which may be used in future clinical translational protocols [15][16][17].…”
Section: Introductionmentioning
confidence: 99%